Negotiating Languages: The Sociolinguistic Dynamics of Balinese, Indonesian, and English in Penglipuran Village - Ni Luh Eka Setyawati; Ni Nyoman Padmadewi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study investigates multilingual practices in Penglipuran Village, Bali, focusing on how Balinese, Indonesian, and English are used in daily tourism-related interactions. Over three months, participatory observation captured natural communication between villagers and tourists. Findings reveal that Balinese is primarily used for internal communication, Indonesian for domestic tourists, and English for foreign visitors, with flexible code-switching depending on context. These results highlight the community’s linguistic adaptability and cultural awareness, emphasising the role of local tour guides as cultural mediators. The study contributes to sociolinguistics in tourism by illustrating how multilingualism supports cultural preservation and enhances sustainable tourism experiences.